Analisis Framing Pemberitaan Putusan Mahkamah Konstitusi: Studi Pada Berita Syarat Usia Calon Presiden Dan Calon Wakil Presiden Di Mahkamah Konstitusi Tahun 2023 - Fadillah, Muhammad Iqbal; Kalaloi, Abdul Fadli; Alwaton, Yogie (eProceedings of Management, 2024)
The Constitutional Court's decision regarding the age limit for presidential and vice presidential candidates wasratified which resulted in a new decision to remain at a minimum age of 40 years but with the addition of the phrase